2020
DOI: 10.1038/s41598-020-78977-w
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of mechanically competent 3D printed polycaprolactone-reduced graphene oxide scaffolds

Abstract: The ability to produce constructs with a high control over the bulk geometry and internal architecture has situated 3D printing as an attractive fabrication technique for scaffolds. Various designs and inks are actively investigated to prepare scaffolds for different tissues. In this work, we prepared 3D printed composite scaffolds comprising polycaprolactone (PCL) and various amounts of reduced graphene oxide (rGO) at 0.5, 1, and 3 wt.%. We employed a two-step fabrication process to ensure an even mixture and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 73 publications
4
54
0
Order By: Relevance
“…Moreover, the rGO-PCL blended composite was amenable to printing under similar conditions to its PCL-only counterpart, indicating that functionalization did not dramatically alter the underlying polymeric thermal characteristics. Importantly, rGO-PCL blends were conducive to printing at structural architecture and pore size resolutions needed to facilitate ECM production and organization, with resulting dimensions similar to those in recently published literature that used alternative solvent methods [56][57][58]. SEM imaging revealed that surface topography for heat-extruded thermoplastics was highly smooth, potentially presenting a difficult attachment surface for cells.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Moreover, the rGO-PCL blended composite was amenable to printing under similar conditions to its PCL-only counterpart, indicating that functionalization did not dramatically alter the underlying polymeric thermal characteristics. Importantly, rGO-PCL blends were conducive to printing at structural architecture and pore size resolutions needed to facilitate ECM production and organization, with resulting dimensions similar to those in recently published literature that used alternative solvent methods [56][57][58]. SEM imaging revealed that surface topography for heat-extruded thermoplastics was highly smooth, potentially presenting a difficult attachment surface for cells.…”
Section: Discussionsupporting
confidence: 51%
“…As the utilized pneumatic additive manufacturing system is commercial, this may provide a more translatable set of print parameters and methodologies than observed with custom printer systems, and reduce optimization times associated with reproducing material constructs [54]. The incorporation of rGO using a simple heated blending process with DMSO removed the need for more aggressive solvents, such as commonly utilized DCM or chloroform [55,56]. This reduced cytocompatibility risks associated with residual solvents and streamlining the material synthesis protocol.…”
Section: Discussionmentioning
confidence: 99%
“…PCL is a Food and Drug Administration (FDA) approved linear polyester with good biocompatibility, slow degradation rate, less acidic breakdown products in comparison to other polyesters, and has the potential for loadbearing applications [ 11 , 12 ]. The slow degradation of PCL allows time for bone remodeling and can also be manipulated to adjust the polymer’s biodegradation rates [ 13 , 14 ]. Additionally, PCL is one of the most preferred polymers for extrusion-based 3D printing due to its melting temperature of 55–60 °C [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The slow degradation of PCL allows time for bone remodeling and can also be manipulated to adjust the polymer’s biodegradation rates [ 13 , 14 ]. Additionally, PCL is one of the most preferred polymers for extrusion-based 3D printing due to its melting temperature of 55–60 °C [ 13 ]. It exhibits good mechanical properties with high flexibility and great elongation, conducive to the preparation of scaffolds for craniofacial bone repair [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Introducing graphenic additives into ceramic matrices presents the possibilities to create rigid ceramic composites, with desired mechanical properties and biological characteristics required for bone regeneration. The high surface area of graphene (2630 m 2 g −1 ) provides a vast area to interact with the surrounding matrix, adsorb proteins, and facilitate cell–ceramic interactions 28 …”
Section: Introductionmentioning
confidence: 99%